USABILITY ANALYSIS OF AN ANDROID BASED VIDEO CONFERENCE APPLICATION - Achmad Azhar Rifan Nugroho; Erwin Apriliyanto (LPPM Universitas An Nuur, 2023)
In the digital age, data and technology are evolving very quickly. Technology is basically the process of adding value to a given outcome and Android is an application platform and an operating system for smartphones. The use of Android is huge in our life, now educators can use Android to improve teaching supported by smartphones and other Android based gadgets like Srawung video conference. This is very important in our life, Srawung video conference is a very useful alternative application as a cloud based virtual conference that aims to easily communicate with many people without direct contact and can support education in the digital age. It has been shown that this case paper analyzes the usability of Srawung video conference application as a tool to support teachers' learning, the results of this usability analysis are expected to provide insights for future development of the application so as to improve the usability of the application. The test includes five aspects of usability, learnability, effectiveness, memoriability, errors, and satisfaction. The results of the study show that the usability value of Srawung version 1.0 is a percentage value of 96.11%, which indicates that the application is very useful.